Eco-Factories of the Future - Thiede, Sebastian; Herrmann, Christoph; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This edited monograph presents a selection of research contributions on eco-factories of the future. The topical focus lies on cutting-edge solutions from academia and industry that enable and support companies in their efforts towards sustainable manufacturing. The authors provide an overview over recent developments, aiming at a comprehensive understanding of eco- and cost-efficient manufacturing from machine to factory level. The solutions contributed by leading research institutions and companies have been mostly implemented and evaluated in industrial pilot projects across Europe. The methodological approaches cover topics such as factory planning, manufacturing simulation, energy management as well as life cycle evaluation. The target audience comprises industry experts and decision makers as well as researchers in the field of sustainable manufacturing.
Towards eco-factories of the future -- Integrating variable renewable electricity supply into manufacturing systems -- Development of a sustainability assessment tool for manufacturing companies -- Sustainability assessment in manufacturing and target setting in highly automated production -- Piloting comprehensive industrial energy efficiency improvement in a european rolling stock factory -- Cyber physical approach for integrated energy and maintenance management -- Two practical approaches to assess the energy demand of production machines -- Analysis of production lines with switch-off/on controlled machines -- Approach for achieving transparency in the use of compressed air in manufacturing as a basis for systematic energy saving.
Keywords: Industrial Management; Sustainability; Energy policy; Energy and state; Technological innovations; Manufactures; Industrial Management; Sustainability; Energy Policy, Economics and Management; Innovation and Technology Management; Machines, Tools, Processes